Near-road traffic-related emission pollutants and characteristics in Petaling Jaya, Selangor, Malaysia - Mohamad, Nur Diyana (2018)
Motor vehicles have always been recognized as the main source of urban air pollution which contribute to deprived air quality. Due to its variation in distribution of air pollution and its significant impact of poor urban air quality and human health effects as well as its limited information of traffic pollution studies in Malaysia, there is a need of assessing the spatiotemporal distribution of traffic-related pollutants so that their impact and exposure variability could be monitored and documented accordingly in order to provide preventive measures and better planning in future. Hence, the objectives of this research are to assess spatial and temporal distributions of near-road pollutant concentration and to estimate the vehicular emissions. The research was conducted at different street categories in Petaling Jaya, Selangor such as local streets, urban streets and highways. Observed vehicle counts and emission factors from United States Environmental Protection Agency (USEPA) of Compilation of Air Pollutant Emission Factors (AP-42) and European Monitoring and Evaluation Program/European Environment Agency (EMEP/EEA) Guidebook were used to estimate vehicular emissions. Ambient concentrations were estimated using geostatistical interpolation technique. The traffic emission data have been collected and investigated prior to traffic flow data. Statistical analysis for both traffic emission and its characteristics as well as meteorological data was conducted and the correlation between them was demonstrated and assessed. Multivariate analysis was then being executed in order to evaluate which meteorological parameters contribute the most to the concentration and dispersion of the pollutant. The final results revealed that most of the concentration of the traffic-related pollutants measured are significantly higher at highways than the urban and local streets due to its high traffic volumes. Results showed that traffic emission on Petaling Jaya streets significantly contributes to poor near-road air quality, except for carbon monoxide concentration. Most of the pollutants show almost the same daily trends of 12-hour period of time at all type of streets. It is assumes that the concentration of pollutants occurred twice a day which spike during the period of rush-hour time; morning rush hour and evening rush hour. The pollutants concentration such as nitrogen dioxide (NO2), carbon monoxide (CO), particulate matter with an aerodynamic diameter of equal to or less than 2.5 microns (PM2.5), and particulate matter with an aerodynamic diameter of equal to or less than 10 microns (PM10) started to peak at 7:00 to 10:00 am and eventually, it decreased slowly during non-rush hour period (10:00 am–4:00 pm) and a rising level of pollutants was experienced in the evening rush hour (4:00 pm–7:00 pm). The study also displayed that most of the Petaling Jaya streets including highways suffer from very high concentrations of gaseous pollutants, primarily caused by the traffic-related pollutants which surpassed a number of standards and guideline maximum limits, except for CO. The highest contributor of pollutant based on the emission calculation is arranged ascendingly with PM2.5 with 0.08%, followed by NO2 (9.17%), PM10 (17.40%), and lastly CO as the highest contributor of pollutants with 73.35% of total emission. Indeed, traffic-related pollution in the urban area basically depends on its spatiotemporal phenomenon. Elevation, meteorological condition and its proximity to high emission sources affect the pollutants’ spatially and temporally which indicate an alarming level of concentration level taking place. In this research, the application of Geographic Information Systems (GIS) proved to be invaluable not only as a data resource and analysis tool but also as an effective means of communicating complex scientific information.